An investigation of the cause of death in Wistar rats exposed to sunlight: focus on tissue histology - Iyanda, Ayobola; Oparinde, Dapo (International Journal of Biological Research, 2014)
Objective: The aim of the study is to investigate the effects of ultraviolet rays of the sun on organs like the liver, brain, heart, kidney, lung and ileum. Methods: Fourteen female rats (235 g) were used for the study and equally distributed into 2 groups. While the rats in the test groups were left in an open place for a period of 7 hours daily for adequate exposure to sunlight, control rats were kept in cages at ambient temperature of 26°C in the animal house. When all the animals died on the 10th day of study, samples of different tissues were obtained, fixed in 10% neutral buffered formalin and stained with hematoxylin and eosin (H & E). Results: 100% mortality was recorded. Results showed no visible lesion for all the tissues of control rats whereas pathological features like severe congestion of the coronary vessel and mild pulmonary congestion as well as thickening of alveolar wall were reported for heart and lung respectively in sun-exposed rats. Moreover, in sun-exposed rats other tissues such as the brain, ileum, kidney and liver showed no visible lesion. Conclusion: From the outcome of this study, it may be inferred that excessive sun exposure can be a cause of mortality in a nocturnal animal species, with death resulting from multi-organ damage. Keywords: Daily Exposure, Mortality, Rat, Sunlight, Tissues.